Pedagogical paradigms: Enhancing 6G learning experiences for future security professionals - Ochoa-Tataje, Freddy (2024)
The guiding concepts, procedures, and strategies that teachers employ to promote learning are known as pedagogical paradigms. They support the entire educational process and have an impact on how knowledge is organized, disseminated, and assimilated by students. Comprehending the importance of pedagogical paradigms is crucial, as they influence students' learning experiences and their capacity to acquire and utilize knowledge efficiently. The primary goal of education is to equip people with the skills and knowledge necessary to meet the opportunities and challenges of both their personal and professional lives.